Evaluación de la Capacidad Territorial Turística Mediante Análisis por Conglomerados: El Caso de la Perla del Pacifico. - Hernández Juárez, José Luis; Pérez Cervantes, Baltazar; Reyes García, Sandra Irene; Urías García, Marine Rosario (Revista Daena: International Journal of Good Conscience, 2016)
This research was made with the objective of evaluating the territorial capacity of a set of touristic areas in the port of Mazatlán Sinaloa. The analyze data considers 573 quantitative variables for the municipality of Mazatlán, which is located in the INEGI bank of information. The investigation results contribute in the construction of a global rating that offers empiric evidence about five dimensions. (Natural, Cultural, Tourist Plant, Tourism Infrastructure, Tourism Superstructure), which provides criteria to identify and defined the degree of suitability that presents the territory from a physical, social, economic and environmental context. To ease the research, it was used the cluster analysis, with base in this five dimensions two main TIPOLOGIAS got identify (tourist areas with high potential and tourist areas with low potential).